Outlets for developing countries in the German market: The scope for national trade policy - Axel Borrmann (Intereconomics, 1979)
As one of the biggest trade partners of the developing countries the Federal Republic of Germany is of necessity one of the states to which these countries will address their trade-political demands at UNCTAD V. An analysis shows however that, as the classic competences for trade policy decisions have been largely transferred to the EC, the Federal Republic is left with very little scope for action.
Keywords: 330; Unctad V